A study of the therapeutic application of Yoga Prana Vidya healing protocols in successful facial healing - Yadav, Shanti; Nanduri, Venkata S. (International Journal of Research in Dermatology, 2025)
The goal of facial rejuvenation procedures is to enhance the skin's appearance by correcting spots, scars, fine lines, wrinkles, and uneven skin tone. These treatments include more intrusive operations like facelifts as well as non-invasive ones like chemical peels and laser therapy. Yoga Prana Vidya (YPV) system facial healing treatments are non-invasive, drug-free and often tailored to address particular issues and produce a range of satisfactory outcomes, from minor enhancements to more significant changes. This study presents successful facial healing cases of two young men aged 30 and 25 using YPV techniques. Multiple case study method is used by collecting data from the two clients and the YPV healer. In both cases using daily healing sessions of 30 minutes each over a period of 3 months, complete and permanent improvements were achieved to the satisfaction of the clients. During a follow up after a year and a half, the two clients reported sustained changes. YPV healing regimens have been shown to be highly beneficial in successfully healing a number of health disorders without the need for pharmaceutical or surgical treatments. Further research utilising suitable samples and methods is advised.